A small interfering RNA targeting vascular endothelial growth factor efficiently inhibits growth of VX2 cells and VX2 tumor model of hepatocellular carcinoma in rabbit by transarterial embolization-mediated siRNA delivery - Zou Y; Guo CG; Yang ZG; Sun JH; Zhang MM; Fu CY (Dove Medical Press, 2016)
Yu Zou,1,2 Chuan-Gen Guo,2 Zheng-Gang Yang,3 Jun-Hui Sun,4 Min-Ming Zhang,5 Cai-Yun Fu6,71Department of Radiology, Women’s Hospital, School of Medicine, Zhejiang University, 2Department of Radiology, First Affiliated Hospital, School of Medicine, Zhejiang University, 3Institute of Infectious Diseases, First Affiliated Hospital, School of Medicine, Zhejiang University, 4Division of Hepatobiliary and Pancreatic Surgery, Department of Surgery, First Affiliated Hospital, School of Medicine, Zhejiang University, 5Department of Radiology, Second Affiliated Hospital, School of Medicine, Zhejiang University, 6College of Life Sciences, Zhejiang Sci-Tech University, 7Key Laboratory of Cell-Based Drug and Applied Technology Development in Zhejiang Province, Hangzhou, People’s Republic of China Introduction: Hepatocellular carcinoma is currently the second leading cause of cancer-related deaths worldwide with an increasing incidence.Objective: The objective of this study is to investigate the effect of vascular endothelial growth factor small interfering RNA (VEGF-siRNA) on rabbit VX2 carcinoma cell viability in vitro and the effect of transarterial embolization (TAE)-mediated VEGF-siRNA delivery on the growth of rabbit VX2 liver-transplanted model in vivo.Methods: Quantitative reverse transcription polymerase chain reaction, enzyme-linked immunosorbent assay, and Western blot technologies were used to detect the expression level of VEGF. TAE and computed tomography scan were used to deliver the VEGF-siRNA and detect the tumor volume in vivo, respectively. Microvessel density was detected by immunohistochemistry with CD34 antibody. A biochemical autoanalyzer was used to evaluate the hepatic and renal toxicity.Results: The designed VEGF-siRNAs could effectively decrease the expression levels of VEGF mRNA and protein in vitro and in vivo. In vitro, the viability of rabbit VX2 carcinoma cells was reduced by 38.5%±7.3% (VEGF-siRNA no 1) and 30.0%±5.8% (VEGF-siRNA no 3) at 48 hours after transfection. Moreover, in rabbit VX2 liver-transplanted model, the growth ratios of tumors at 28 days after TAE-mediated siRNA delivery were 155.18%±19.42% in the control group, 79.67%±19.63% in the low-dose group, and 36.09%±15.73% in the high-dose group, with significant differences among these three groups. Microvessel density dropped to 34.22±4.01 and 22.63±4.07 in the low-dose group and high-dose group, respectively, compared with the control group (57.88±5.67), with significant differences among these three groups. Furthermore, inoculation of VX2 tumor into the liver itself at later stage induced significant increase in alanine aminotransferase and aspartate aminotransferase, indicating an obvious damage of liver functions, while treatment of VX2 tumor via TAE-mediated VEGF-siRNA had no toxicity to the livers and kidneys of rabbits, and VEGF-siRNA had the ability to protect liver damage induced by tumor growth.Conclusion: This is the first study to demonstrate that targeting VEGF via TAE-mediated siRNA delivery may become a powerful new option for effective treatment of hepatocellular carcinoma in the clinic.Keywords: hepatocellular carcinoma, VEGF-siRNAs, CT scan, microvessel density, toxicity to the livers and kidneys